Development of the Preliminary Numerical Model of the Short Recoil Operated Weapon Using the Multibody Systems - Przemysław BADUROWICZ (Opracowanie wstępnego modelu numerycznego broni działającej na zasadzie krótkiego odrzutu lufy z zastosowaniem metody układów wieloczłonowych, 2021)
The paper contains a literature review of studies on several firearms operation systems and a review of articles on modern methods of calculating the kinematic characteristics of weapons. It includes the presentation of the short recoil operated 9 mm PW INKA pistol numerical model. The model was created in the MCS Adams software which uses the multibody systems. The boundary conditions for each part were specified and their implementation was determined. As the preliminary results of numerical investigations, the slide and barrel velocity and displacement curves were obtained. Comparison of a numerical solution with the literature data allowed for its qualitative verification.
Keywords: Modelowanie działania broni automatycznej